The surgical management of patients with clinical stage T4 bladder cancer: A single institution experience. Issue 4 (April 2017) - Moschini, M.; Luzzago, S.; Zaffuto, E.; Dell'Oglio, P.; Gandaglia, G.; Mattei, A.; Damiano, R.; Soria, F.; Klatte, T.; Shariat, S.F.; Salonia, A.; Montorsi, F.; et al.
Abstract: Introduction: Patients with clinical T4 (cT4) bladder cancer (BCa) infrequently undergo radical cystectomy (RC). We investigated the reliability of preoperative clinical staging, perioperative and survival outcomes in patients treated with RC due to cT4a-b BCa disease at a single tertiary care institution. Methods: The study relied on 917 BCa patients treated with RC and pelvic lymph node dissection (PLND) at a single institution between January 1995 and December 2012. We compared the accuracy of the clinical assessment with final pathology results. Moreover, we evaluated perioperative outcomes, complication rates and survival after surgery. Results: The median follow-up was 62 months. Overall, 74 (8.1%) patients presented cT4 stage at preoperative evaluation. Conversely, a pathological T4 disease was confirmed only in 68.9% patients staged initially as cT4. No differences were recorded in complications, 30 days readmission or 30 days death rates between cT1–T3 vs. cT4a vs. cT4b (p > 0.1). At multivariable Cox regression analyses predicting cancer specific mortality, clinical T4 stage vs. clinical T1–2, clinical T3 stage vs. clinical T1–2 and age were predictors of worst survival after RC (all p < 0.04). Conclusions: We recorded poor concordance between preoperative imaging and pathology in cT4 patients. No differences in major perioperative outcomes and acceptable survival expectancies were reported in patients treated for cT4 disease.